OPTIMIZATION OF PHARMACO-PHYSIOTHERAPEUTIC METHODS IN THE TREATMENT OF ATOPIC DERMATITIS IN CHILDREN - Achilova Donokhan Nutfullaevna; Nasimova Iroda Yakhyaevna (Web of Journals Publishing, 2025)
This article discusses the optimization of pharmacological and physiotherapeutic methods in the treatment of atopic dermatitis in children. Based on the results of the study, the most effective therapy methods are identified.
Keywords: atopic dermatitis, children, pharmacotherapy, physiotherapy, immunological mechanisms.